Present-day breeding of legumes and groat crops in Russia - V. I. Zotikov; S. D. Vilyunov (Вавиловский журнал генетики и селекции)
The production of pedigree seeds is not only an important but also a cost-effective means of increasing the yield and efficiency of agriculture. The genetic potential of varieties can be unlocked only by choosing those adaptive to the soil and climatic conditions in a particular region, using modern tools for plant protection, and applying balanced mineral nutrition. These are the most important factors determining the performance. In the course of breeding and genetic work, the Federal Scientific Center of Legumes and Groat Crops (FSC LGC) has created new soybean varieties, whose high biological and economic potentials are combined with resistance to stress factors. Despite the close relationship between productivity and growing season duration, the highly productive and early-ripening (100–115 days) soybean varieties raised at FSC LGC can yield 2.5 to 3.5 t/ha, the grain having high contents of protein (37–42 %) and fat (18–22 %), depending on the climatic conditions in a particular year of cultivation. They are less temperature-sensitive than other domestic or foreign varieties. It is important that our soybean varieties are not genetically modified. New pea varieties created at FSC LGC in 2015–2020 differ in growing season duration and morphological features. They are adaptable to the soil and climatic conditions of a region, which ensures the maximum realization of their potential. The main factor in increasing yields and stabilizing the production of buckwheat and millet grain in the Russian Federation is the creation and adaption of new earlyripening and high-yielding varieties of the determinate type adapted to the specific natural and climatic conditions of different regions of Russia.